2007
DOI: 10.1093/toxsci/kfm276
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide-Responsive Genes in the Nematode Caenorhabditis elegans

Abstract: As acrylamide is a known neurotoxin for many animals and potential carcinogen for humans, it came as a surprise when the Swedish National Food Agency and Stockholm University reported in 2002 that it is formed during the frying or baking of foods. We report here genomic and proteomic analyses on genes and proteins of Caenorhabditis elegans exposed to 500 mg/l acrylamide. Of the 21,120 genes profiled, 409 genes were more than twofold upregulated and 111 genes were downregulated. Upregulated genes included many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 40 publications
2
76
1
Order By: Relevance
“…Accordingly, an in vitro study showed no influence of GSTM1 or GSTT1 on hemoglobin adduct formation after exposure of human blood samples to acrylamide and glycidamide (75). However, recently the up-regulation of genes encoding GSTs was shown by exposure of Caenorhabditis elegans to 500 mg/L acrylamide, and proteomic analysis confirmed some involvement of GSTs (26). Negative results from our study on the influence of GSTs on acrylamide metabolism support the hypothesis of a primarily nonenzymatic conjugation of acrylamide and glycidamide with glutathione (75).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, an in vitro study showed no influence of GSTM1 or GSTT1 on hemoglobin adduct formation after exposure of human blood samples to acrylamide and glycidamide (75). However, recently the up-regulation of genes encoding GSTs was shown by exposure of Caenorhabditis elegans to 500 mg/L acrylamide, and proteomic analysis confirmed some involvement of GSTs (26). Negative results from our study on the influence of GSTs on acrylamide metabolism support the hypothesis of a primarily nonenzymatic conjugation of acrylamide and glycidamide with glutathione (75).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, AAMA, its sulfoxide, and GAMA have been unequivocally confirmed in humans (9)(10)(11). Whereas there are many glutathione-S-transferases (GST) in humans and rodents, which may be involved in these metabolic steps, nonenzymatic formation of glutathione conjugates is also possible and has been reported for acrylamide (25,26). The role of GSTs in acrylamide metabolism in humans remains to be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Paraquat is a synthetic, contact herbicide used throughout the world in agricultural applications (Powles and Yu, 2010). Acrylamide is not likely to affect C. elegans in nature, but it is a strong inducer of SKN-1 transcriptional activity (Hasegawa et al, 2008) and produces oxidative stress in other organisms (Prasad and Muralidhara, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The wet sediment was then divided among four 20 mL syringe cylinders plugged with a stainless steel mesh disc and glass wool (Hasegawa et al, 2008). The cylinders were placed in 50 mL plastic tubes and centrifuged at 4,500 g for ten min.…”
Section: Aqueous Extractsmentioning
confidence: 99%
“…GSTs consists of ubiquitous, dimeric proteins involved in the detoxification of endogenous and xenobiotic compounds by glutathione conjugation, peroxidase activity or passive binding, supporting the conversion of GSH to electrophilic GS À , which binds to toxic compounds and leads their excretion (Campbell et al, 2001). Among them, gst-1 and gst-4 are strongly inducible by organic compounds (Hasegawa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%